Tuning of virgin coconut oil and propylene glycol ratios for maximizing the polyphenol recovery and in vitro bioactivities of mangosteen (Garcinia mangostana L.) pericarp. (December 2019) - Sungpud, Chatchai; Panpipat, Worawan; Sae Yoon, Attawadee; Chaijan, Manat
Graphical abstract: Highlights: The extraction efficacy of MP phenolic by VCO was improved by PG addition. VCO with 40–70% PG enhanced the recovery of TPC, TFC, α-mangostin and γ-mangostin. α-mangostin, γ-mangostin, rutin, vanillic acid and (-) epicatechin were identified. Phenolic profile markedly affected bioactivities of MP extract. Mixed solvents can improve ˜3–7 times of in vitro bioactivities compared to VCO alone. Abstract: The extraction efficacy of polyphenol from magosteen ( Garcinia mangostana L.) pericarp (MP) using virgin coconut oil (VCO) can be improved using propylene glycol (PG). In this study, VCO to PG ratios of 100:0, 70:30, 60:40, 50:50, 40:60, 30:70, and 0:100 (w/w) were used. The MP extracts were analyzed for the total phenolic content (TPC), total flavonoid content (TFC), phenolic profiles and the in vitro bioactivities. From the results, an incorporation of 40–70% PG into VCO could effectively improve the recovery of TPC, TFC, α-mangostin and γ-mangostin. The antioxidant, antibacterial and antidiabetic activities of MP extracts obtained by incorporating 30–70% PG into VCO were also improved or even equivalent to the extract obtained by pure PG. From the safety and cost effective points of view, 40–50% PG can be mixed with VCO for extraction of MP phenolic. The MP extracts can be potentially used for a wide range application in food, pharmaceutical, and cosmetic without solvent removal.